PENGARUH AKTIVITAS FISIK JALAN PAGI TERHADAP STABILITAS TEKANAN DARAH LANSIA DI PSTW KHUSNUL KHOTIMAH PEKANBARU - Mustika " Riolita; Gamya Tri Utami; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract People’s age will lead to change of the physiological one. One of the physical deterioration that often occurs deterioration of the cardiovascular system. Physical activity is an active actions that activates the metabolism and produce influence on the operation of the glands in the body's immune system to the body of stable disease, blood pressure and stores them. One of  elderly physical activity is walking in the morning. This study aims to determine the effect of stability physical morning activity of blood pressure in the elderly.Tthe sample are  30 elderly using study design "quasy experiment" with "non-equivalent control group", which is divided into an experimental group and control group. Study was conducted in elderly PSTW Khusnul Khotimah Pekanbaru using purposive sampling technique. Measuring instrument used the observation. The analysis used univariate and bivariate the Mann-Whitney and Wilcoxon. The results of this study showed a decrease in average blood pressure in the experimental group after a certain physical exercise on the morning with p-value (0.001) <α (0.05). This means that the provision of physical activity, an effective way to stability in the morning  blood pressure. The results of this study are expected to healthcare appropriate a good exercise for the elderly. Keywords: elderly, blood pressure, physical activity morning